Actuarial Technique of Modelling the Out of Pocket with Deductible and Stop Loss in Health Care Insurance - Michael, Ogungbenle Gbenga (Nepal Journal of Mathematical Sciences, 2021)
The paper is intended to numerically estimate health insurance out of pocket spending from the perspective of the enrollees in order to inform whether health insurance scheme pricing policy delivers value to the enrollees. We study the implications of financing health care insurance using a classification model for health care insurance under the framework of deductibles and stop loss. The paper is designed for health underwriting professionals, particularly those who consult for health insurance schemes. This is essential given the form and emergence of treating enrollees fairly, based on regulations that impact on actuarial consultants advising on health insurance scheme product lines. The objectives of this paper are to demonstrate actuarial methods for estimating (i) total health expenses (ii) out of pocket costs (iii) reimbursements by third party insurance. (iv) examine the actuarial implications of the chosen model. In computing the out of pocket and reimbursement, the Pitacco’s model was adopted because of its relatively computational superiority and the fact that both deductible and stop loss form its core parameters. Our results show that there is a positive relationship between total health expense and the share funded by out of pocket spending. As the health expenditure increases, the share funded by out of pocket progressively increases.